Cystoid edema, neovascularization and inflammatory processes in the murine Norrin-deficient retina - Beck, Susanne C.; Feng, Yuxi; Hammes, Hans-Peter (Scientific reports, 2018)
Mutations in the Norrin (NDP) gene cause severe developmental blood vessel defects in the retina leading to congenital blindness. In the retina of Ndph-knockout mice only the superficial capillary network develops. Here, a detailed characterization of this mouse model at late stages of the disease using in vivo retinal imaging revealed cystoid structures that closely resemble the ovoid cysts in the inner nuclear layer of the human retina with cystoid macular edema (CME). In human CME an involvement of Müller glia cells is hypothesized. In Ndph-knockout retinae we could demonstrate that activated Müller cells were located around and within these cystoid spaces. In addition, we observed extensive activation of retinal microglia and development of neovascularization. Furthermore, ex vivo analyses detected extravasation of monocytic cells suggesting a breakdown of the blood retina barrier. Thus, we could demonstrate that also in the developmental retinal vascular pathology present in the Ndph-knockout mouse inflammatory processes are active and may contribute to further retinal degeneration. This observation delivers a new perspective for curative treatments of retinal vasculopathies. Modulation of inflammatory responses might reduce the symptoms and improve visual acuity in these diseases.